An annotated checklist of the genus Eupithecia Curtis, 1825 (Lepidoptera, Geometridae) of Uzbekistan with description of a new species - Mironov, Vladimir G.; Naydenov, Artem E.; Makhov, Ilya A. (Zootaxa, 2026)
The article provides an annotated checklist of 26 species of geometrid moths of the genus Eupithecia Curtis, 1825, recorded from Uzbekistan. For some species, illustrations of adults and genitalia are included. A new species from the Kugitang Range is described and illustrated: Eupithecia kugitangica Mironov & Naydenov sp. nov. Two species, namely Eupithecia illaborata Dietze, 1904 and Eupithecia kostjuki Mironov, 1989 are reported for the first time from the fauna of Uzbekistan.